2019
DOI: 10.1017/aog.2019.23
|View full text |Cite
|
Sign up to set email alerts
|

Narrowband signals recorded near a moulin that are not moulin tremor: a cautionary short note

Abstract: Geophysicists that deploy seismic sensors in ablation zones of glaciers and ice sheets to record glaciogenic signatures can confront recording challenges caused by instrument melt-out or tilt. These challenges often require installing sensors in boreholes to delay melt-out, or securing sensors to structures that improve coupling. We show that some of these structures that were buried near a moulin at a snow-free site in the ablation zone of the Western Greenland Ice Sheet resonated as they became exposed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…These Dry Valley glaciers are characterized by low ablation rates and limited surface meltwater; therefore, on-ice stations are more likely to remain buried, unflooded and well-coupled to the ice than in other glacial settings. Land-based stations remain useful in cases where on-ice sensor coupling is lost and results in compromised data (Carmichael, 2019) and when they can create a favorable network geometry to study specific source locations of interest. For wintertime seismic investigations, land-based stations may be preferable to on-ice installations if our study is representative of other sites.…”
Section: Does Seismometer Deployment Site Matter?mentioning
confidence: 99%
See 1 more Smart Citation
“…These Dry Valley glaciers are characterized by low ablation rates and limited surface meltwater; therefore, on-ice stations are more likely to remain buried, unflooded and well-coupled to the ice than in other glacial settings. Land-based stations remain useful in cases where on-ice sensor coupling is lost and results in compromised data (Carmichael, 2019) and when they can create a favorable network geometry to study specific source locations of interest. For wintertime seismic investigations, land-based stations may be preferable to on-ice installations if our study is representative of other sites.…”
Section: Does Seismometer Deployment Site Matter?mentioning
confidence: 99%
“…Dalban Canassy and others (2012) similarly describe a correlation between STA/LTA detection capability and modeled glacier runoff over day- to week-periods. Therefore, temporal variability in waveform detection capability has the potential to bias an observer's interpretation of the temporal variability in icequake activity (Röösli and others, 2014; Carmichael, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the HF, repetition, and regularity of the signal, we suspect cultural (anthropogenic) sources or a nearby natural source(s). For example, poles and equipment left in the field can have harmonic seismic signatures that resemble the seismic signatures of moulins (Carmichael, 2019). In addition, previous studies (Allstadt & Malone, 2014) have shown that repeating signals could be due to snow loading.…”
Section: Discussionmentioning
confidence: 99%
“…For the northwest Greenland site, the signal is detected by both the small-aperture array and the remote array 1 km away; therefore, we can rule out sources unique to only the small-aperture array as the remote stations also record the signal. Previous studies in the cryosphere found that poles left in the field as markers could create HF signals (Carmichael, 2019). At both the small-aperture array and remote stations, bamboo poles were left in the field in order to help locate the stations.…”
Section: Vhf Detections (>20 Hz)mentioning
confidence: 99%
“…Ensuring the stability of instrumentation on the surface of glaciers is notoriously challenging (Carmichael, 2019). As a result, most seismic deployments in the ablation zone of glaciers, for example, only cover spatial apertures on the order of 1 km (e.g.…”
Section: Das Offers a Stable Observation Platform On Melting Glacier ...mentioning
confidence: 99%